Методи застосування програмно-конфігурованого радіо (SDR) у мережах мобільного зв’язку перспективних поколінь - Жуга, Ю. С.; Москалець, М. В. (ХНУРЕ, 2023)
Software-Defined Radio (SDR) has shown significant potential in advancing mobile networks for future generations. This research investigates the various methods of implementing SDR in such networks, emphasizing its adaptability and compatibility. It delves into the influence of frequency, sample rate, and signal-to-noise ratio (SNR) on SDR's performance and efficiency.
Keywords: програмно-конфігуроване радіо; SDR